BENEFIT OF ACCOUNTING INFORMATION ON SHARE RETURN - Erita Nur Andini; Author; Farhan Ramdhani Yanza; Febriani Pratama Putri; Suryana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the Benefit of Accounting Information on Share Return. The research population is the Property and Real Estate Sub-sector which is listed on the Indonesia Share Exchange (BEI) for the 2017-2019 period. Sampling using a purposive judgment sampling technique of 30 companies with a total of 90 annual observations with criteria for companies that meet the criteria. The analysis technique used is panel data regression with the Common Effect Method (CEM) and hypothesis testing using t-statistics to test the partial regression coefficient. This type of research explanatory uses path analysis processed with the Eviews 11 program. The findings of this study are that the exchange rate and interest rate variables affect partially the variable share return. Meanwhile, the Return On Asset variable does not partially affect the variable Share Return.